RANCANG BANGUN ALAT PENGADUK ADONAN BUBUR ORGANIK KAPASITAS 7 LITER UNTUK INDUSTRI UMKM - Ahmad Yunus Nasution; Gunawan Hidayat (University of Muhammadiyah Jakarta, 2018)
In today's era that is sophisticated and requires speed in the industrial world, humans are required to make and design various tools to get maximum results compared to the manual work of human strength. As an example that can be done instantly and without the need for human labor in the industrial world is the design of a slurry mixer, so that when cooking and stirring the slurry can be faster and more efficient. One of them during the stirring process can reduce the amount of production costs for employees. This study aims to plan and make a transmission and rotation system on a 7 liter capacity slurry mixer for umkm. As for the background of this research because Indonesia is one of the countries that has many SME sectors that have very large opportunities to be developed in the future. This study uses calculations for the slurry stirrer transmission system. The calculation includes an electric motor with a power of 1hp output speed of 1400 rpm with a gearbox ratio of 1:20 and with the size of the drive pulley is 2 in or 50.8 mm and the drive pulley is 4 in or 101.6 mm, the final speed is 35 rpm. The belt used is a V type A belt with a length of 914 mm. The shaft used is 25 mm in diameter with SS304 material.